2018
DOI: 10.3390/molecules23071828
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Nematicidal Compounds against the Pine Wood Nematode, Bursaphelenchus xylophilus through an In Silico Approach

Abstract: Bursaphelenchus xylophilus is a destructive phytophagous nematode that mainly infects pine species and causes pine wilt disease (PWD). PWD is one of the most devastating diseases that has damaged the pine forests of eastern Asia and Portugal for the last four decades. B. xylophilus infects healthy pine trees through Monochamus beetles and its subsequent proliferation results in destruction of the infected pine trees. The poor water solubility and high cost of currently used trunk-injected chemicals such as ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For example, in the fungus Fusarium oxysporum , 2,4-di- tert -butylphenol, a compound that effectively inhibits spore germination and hyphal growth in vitro, was discovered through molecular docking analyses to potentially bind to β-tubulin protein at the HIS 118 and THR 117 residues [17]. In the plant parasitic nematode Bursaphelenchus xylophilus , the compounds amocarzine, mebendazole, and flubendazole were revealed to bind various target sites, including β-tubulin, by analyzing hypothetical binding sites in a protein model constructed through molecular docking [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the fungus Fusarium oxysporum , 2,4-di- tert -butylphenol, a compound that effectively inhibits spore germination and hyphal growth in vitro, was discovered through molecular docking analyses to potentially bind to β-tubulin protein at the HIS 118 and THR 117 residues [17]. In the plant parasitic nematode Bursaphelenchus xylophilus , the compounds amocarzine, mebendazole, and flubendazole were revealed to bind various target sites, including β-tubulin, by analyzing hypothetical binding sites in a protein model constructed through molecular docking [18].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic non-bonded interactions are formed with Pro42, His191, and Phe218 (Figure 3c). Generally, the non-bonded interaction is involved in making the protein-ligand complex more stable and establishing non-bonded force (Vander Waal’s) to make the ligands achieve its stable conformation for better activity [38].…”
Section: Resultsmentioning
confidence: 99%
“…Further, advancement in the bioinformatics assisted molecular and dynamics simulation studies can also help to decipher the molecular and biochemical mechanisms. Moreover, several reports have already been initiated on the structure prediction and their possible interaction with different cellular protein/enzyme targets [207][208][209][210]. Cob-Calan et al [211] demonstrated the interactions of the cyclic lipopeptides iturin A, fengycin, and surfactin with β-tubulin using molecular docking and molecular dynamics simulation.…”
Section: Future Prospects Of Microbial Lipopeptides In Plant Disease mentioning
confidence: 99%